Gallery Walk activities in ESL classrooms / Amiza Hazni Mohd Radzi ... [et al.] - Mohd. Radzi, Amiza Hazni; Othman, Anita; Mohd Radzi, Amizura Hanadi (Universiti Teknologi MARA, Kedah, 2020)
The purpose of this study was to examine the perceptions of students towards Gallery Walk and how Gallery Walk can be used as a tool to enhance students' speaking skills. The research methodology integrated the Convergent Parallel Mixed Methods Design. This study involved an Intact Group which consisted of 16 Perlis Matriculation College students. The instruments employed in this study were questionnaires and focused group interviews. Descriptive data analysis was utilized to analyse the data collected using questionnaires. The researchers also collected data from the participants by utilizing focused group interviews. Findings from the study showed that majority of the participants had positive perceptions towards the use of Gallery Walk in enhancing their speaking skills. Gallery Walk activity also incorporated the use of ICT as a way to promote quality education, i.e. Sustainable Development Goal (Goal: 4). Through Gallery Walk, students' confidence to speak English was also heightened as they actively involved by exchanging responses while completing the task assigned to them. Therefore, the findings of the study are hoped to provide insights for academicians to integrate the strategy of using Gallery Walk in ESL speaking classes to enhance students' speaking skills.